Role of Top & Middle Management Support and Strategic Purchasing In Gaining Competitive Advantage: Mediation of Internal Supply Chain Management - Narong Kunides; Norawat Charoen Rajapark (International Journal of Supply Chain Management, 2019)
In modern globalized era with a lot of consistent fluctuations, the need for a unique and long terms competitive advantage (CA) has become crucial. In response to the need for researches on drivers of CA, the purpose of the present study is to investigate the impact of TMMS and purchasing strategy on the internal SCM of the firm and then the ultimate impact of internal SCM on competitive advantage of the firm. The study was performed quantitatively to analyze relationships and the relationships were supported through theory of SCM. The data for the current study was gathered from managerial level employees of firms included in the sample. The analysis revealed that strategic purchasing as well as TMMS has significant positive influence on the internal SCM. It is further revealed that the internal SCM plays a significant role of mediator between strategic purchasing and SCM and between TMMS and CA. These findings and discussion of the current study have important theoretical and practical contributions.